Spectrophotometric Quantification of Endogenous Salicylic Acid in Priming Wheat Tissue with Puccinia Triticina F. Sp. Tritici - Abdalla El-Alwany; Abdelhakim Banni (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. To prove the importance of application exogenous SA that leading to accumulation of endogenous SA as an indicator to the initiation of SAR, by measuring the levels of endogenous SA in priming wheat plant. Methods. The experiment was conducted in complete randomized block design, by planting two basins, at a rate of 300 wheat seeds in each basin. Place and Duration of Study. This study was conducted at research station farm of the agriculture faculty in Soluqe area, between December 2020 and April 2021. Fungal spores and extraction: spores of Puccinia triticina f. sp. tritici were harvested and inoculated in Wheat plants sprayed with Salicylic acid or distilled water. Wheat leaves were extracted in ethanol solvent. Samples were swirled well in the solvent followed by centrifugation at 10,000 g for 10 min. Absorbance was measured using UV-Visible spectrophotometer at wavelength of 540nm against blank sample (without salicylic acid) to determines the SA concentration, disease incidence and severity were measured too. Results. Endogenous SA values were ascending dramatically from 10 days to 20 days with significant differences, while control plants exhibit lower values in all day’s periods, insignificantly. SA treatments proved reduction in disease incidence after 10 days with 50% and after 20 days 45.4%, while after 30 days the reduction recorded high percentage of 63.6%. In comparison between the time intervals, it is clear the severity reduced by 70.9% after 10 days of inoculation and by 71.9% after 20 days, but the reduction was the highest by 80.8% after 30 days of inoculation. Conclusion. We proved the reduction of wheat leaf rust incidence and severity as a result of treatment with 1mM of SA, leading to accumulation of significant levels of endogenous SA; the key role in initiation of systemic acquired resistance.